PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA - Ardiansyah, Ardiansyah; Faelasofi, Rahma (JURNAL e-DuMath, 2019)
Abstrak Match is one subject which has important role in daily live. In implementing of learning by using drill method, the students have better level in understanding the material. It caused the students have the experience and routine practice in understanding match concepts for themselves even it has done individually or in group. The formulation of problem of in this research is how students score in drill method implementation? This research objective is to describe implementation of drill method in correction and function materials and to know characteristic of KKM students score. This research is action research. The subject of research is students of VIII-5 SMP Muhammadiyah Pringsewu Lampung Kabupaten Pringsewu. Based on the result of analysis data in cycle 1, the result of students score was 34,38%. Whereas students score in cycle 2 improved with score 53,12%, so the improving was 87,5%. Based on KKM percentage result it can be determined completely and it can conclude that students score of VIII-5 SMP Muhamamdiyah Pringsewu Lampung improved in using drill method. Keywords: mathematic learning, students’ learning achievement, drilling method